Fiberglass versus cast metal posts: a practical review based on mechanical properties - Corazza, Pedro Henrique; Di Domênico, Marielle Bazzo; Facenda, Júlia Cadorim; Merlo, Erlon Grando; Borba, Marcia; Ozcan, Mutlu (Brazilian Dental Science, 2022)
The current review aimed to compare the mechanical properties and clinical behavior of fiberglass and cast metalposts. It included in-vitro studies, finite element analysis, clinical studies, and systematic reviews that evaluatedfiberglass and metal posts with reliable methodologies. The reports in the literature diverge on tooth failure modesand stress distributions in the root according to different posts. Investigations suggest that fiberglass posts arepreferable because their elastic modulus is similar to dentin. Other studies mention that the flexibility of fiber postsmay damage the interface. The fracture load values of different studies could not be compared. The presence of aferrule seems beneficial. Cast metal posts provide higher characteristic strength to the set but with more unfavorablefailures. Intraradicular posts with a lower elastic modulus produce more stress between the cement layer and dentin.In conclusion, fiberglass and cast metal posts can be used with a ferrule. Cast metal posts seem more appropriatefor weakened teeth. The presence of a ferrule benefits the system. Weakened teeth tolerate higher loads whenrestored with cast metal posts, but when these posts fail, the only solution is tooth extraction. Clinical follow-upscannot yet detect differences between the survival rates of intraradicular fiberglass and cast metal posts.KEYWORDSFiberglass; Post and core technique; Dental prosthesis; Mechanical tests; Finite element analysis.